Academic Supervision of Planning and Implementation of Arabic Language Learning - Arsal, Fathur Riyadhi; Hidayat, D.; Syafe'i, Isop (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
The Madrasah head is responsible for organizing and implementing supervision activities in an effort to improve and enhance the teacher-learning process. The study aims to determine academic supervision on Arabic language learning planning and implementation at MTsN 1 Makassar City. The research uses a descriptive method, and the qualitative approach uses Nvivo12. Results showed that the head of the madrasah and senior Arabic teachers work together to conduct academic supervision, which includes carrying out Arabic lesson planning supervision through direct supervision and indirectly, which is carried out through the Arabic MGMP forum. In addition, MTsN 1 Makassar City also invites education practitioners to help guide teachers. Then, in supervising the implementation of Arabic learning, the Head of Madrasah, in collaboration with the MGMP coordinator, conducts classroom visits to observe the administration and implementation of learning. In the course of learning, if teachers are found to have difficulties, they will be directed and assisted in the Arabic MGMP forum. Implication of research is the emphasis on the important role of madrasah principals in organizing and implementing supervision activities, strengthening collaboration between madrasah principals and senior Arabic teachers and focusing on supporting teachers who experience difficulties, both through direct direction and assistance in the Arabic MGMP forum.